Method of measuring entering beam parameters of the cyclotron U-240 stable isotope separator - O. E. Valkov; O. V. Dubinin; O. K. Zaichenko (Ядерна фізика та енергетика)
Method of measuring of the beam parameters at the entrance of the ion-optical tract of the cyclotron U-240 stable isotope separator is described.